Silver Nanoparticles Mediated by Natural Extracts Recovered from Wastes and By-Products - Cristian Moisa; Andreea I. Lupitu; Adriana Csakvari; Dana Radu; Dorina Chambre; Lucian Copolovici; Dana Maria Copolovici (Chemistry Proceedings, 2022)
Introduction: Current environmental problems demand an eco-friendlier approach to the chemical synthesis of metal nanoparticles (NPs) [...]